Failed high tibial osteotomy: A joint preserving alternative to total knee arthroplasty - Jones,GG; Clarke,S; Jaere,M; Cobb,JP (Orthopaedics and Traumatology: Surgery and Research, 2019)
High tibial osteotomy is an attractive treatment option for young active patients wishing to return to high-level activities. However, it is not considered a long-term solution, with 30% revised at ten years. Currently, the only revision option is a total knee arthroplasty, a procedure that might not deliver the functional level expected by these highly active patients. This paper describes a novel joint preserving approach to HTO revision, using assistive technology, in the form of 3D printed guides, to reverse the osteotomy and simultaneously perform a unicompartmental knee replacement. The indications and planning aims for this procedure are discussed, and the preliminary results in four patients presented.